Avaliação in vitro da atividade antimicrobiana de diferentes soluções a base de hidróxido de cálcio - Seabra, Eduardo José Guerra (2009)
The science of Dentistry wishes obtains the ideal solution for the dental plaque chemical control. This research evaluated antimicrobial action capacity in calcium hydroxide and tergentol various solutions starting for the CHD 20, a root canals irrigating solution with a reason of 80% calcium hydroxide saturated solution and 20% tergentol detergent with the aim of evaluate this drug mouth rinse indication with prevention or combat objective for dental caries and periodontal diseases. Antibiogram disks and biofilm tests were accomplished for the microorganisms: Streptococcus mutans, Streptococcus sanguis, Streptococcus sobrinus and Lactobacillus casei. Different reasons of detergent for the calcium hydroxide saturated solution, tergentol and distillated water solution, 0,12% clorhexydine digluconate solution was positive control and distillated water was negative control. The results showed better performance of clorhexydine in relation to calcium hydroxide directing to not accept this (CHD20) as mouth rinse solution